2007
DOI: 10.1038/sj.hdy.6800928
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin affects fluctuating asymmetry of molar shape in mice, and an epistatic interaction of two genes for molar size

Abstract: Fluctuating asymmetry (FA), random variation between left and right sides in a bilaterally symmetrical character, is a commonly used measure of developmental instability that is expected to increase with increasing environmental stress. One potential stressor is 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), a powerful toxicant known to disturb tooth development. In this study, mice in the F 2 generation produced from an intercross between two inbred strains (C57BL/6J and AKR/J) were exposed in utero to TCDD. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Some of the endpoints of TCDD toxicity such as alterations in heart and craniofacial development also have been observed in mammals (Allen and Leamy, 2001; Ikeda et al, 2000; Ivnitski et al, 2001; Keller et al, 2007; Thackaberry et al, 2005a, 2005b;) and may have implications for human health. The adverse effects of TCDD and PCB 126 on zebrafish larval heart development resemble hypoplastic left heart failure in human newborns (Grimes et al, 2008).…”
Section: Relevance Of Tcdd Toxicity In Zebrafish To Human Healthmentioning
confidence: 99%
“…Some of the endpoints of TCDD toxicity such as alterations in heart and craniofacial development also have been observed in mammals (Allen and Leamy, 2001; Ikeda et al, 2000; Ivnitski et al, 2001; Keller et al, 2007; Thackaberry et al, 2005a, 2005b;) and may have implications for human health. The adverse effects of TCDD and PCB 126 on zebrafish larval heart development resemble hypoplastic left heart failure in human newborns (Grimes et al, 2008).…”
Section: Relevance Of Tcdd Toxicity In Zebrafish To Human Healthmentioning
confidence: 99%
“…In a follow‐up experiment, Keller et al. () found an increase in FA in molar shape but not size. Earlier works investigated the effect of different kinds of stressors, such as heat, cold, noise, and behavioral modification in dental characters and long bones in mice and rats exposed to stress for varying perinatal periods, reporting, in general, an increase in dental asymmetry with stress and a mix of positive and negative results for limb bones (Siegel and Smookler, ; Siegel and Doyle, , , ; Doyle et al., ; Siegel et al., ; Gest et al., ).…”
Section: Introductionmentioning
confidence: 97%
“…Not all toxins affect fluctuating asymmetry of shape: an experiment showed that even applications of sodium pentachlorophenate that were sufficiently severe to suppress cranial growth of zebrafish did not produce increased fluctuating asymmetry of shape [137]. Administering TCDD had no effect on fluctuating asymmetry of shape in mouse mandibles, but affected average shape [43], whereas the same toxin both increased fluctuating asymmetry and changed the average shape of molar teeth [373].…”
Section: Developmental Instability Of Shape In Relation To Stress Andmentioning
confidence: 99%